1990
DOI: 10.1099/0022-1317-71-6-1313
|View full text |Cite
|
Sign up to set email alerts
|

Four major antigenic sites of the coronavirus transmissible gastroenteritis virus are located on the amino-terminal half of spike glycoprotein S

Abstract: Four major antigenic sites have been delineated on the spike protein (S) of the porcine enteric coronavirus transmissible gastroenteritis virus (TGEV) in previous topological studies using monoclonal antibodies (MAbs). Correlation of these sites with the physical structure of the protein was achieved by use of different approaches. Recombinant pEX plasmids directing the synthesis of various fused S polypeptides were constructed. A hybrid protein containing nine S-specific residues (363 to 371) was shown to exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
99
1

Year Published

1990
1990
2002
2002

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(107 citation statements)
references
References 27 publications
7
99
1
Order By: Relevance
“…5). The sequence unique to TGEV S includes the 180 residue long segment where the antigenic site D has been mapped (Delmas et al, 1990). This finding is consistent with the observed lack of reactivity of Purdue site D-specific MAbs towards three different PRCV isolates (Laude et al, 1988).…”
Section: Discussionsupporting
confidence: 77%
“…5). The sequence unique to TGEV S includes the 180 residue long segment where the antigenic site D has been mapped (Delmas et al, 1990). This finding is consistent with the observed lack of reactivity of Purdue site D-specific MAbs towards three different PRCV isolates (Laude et al, 1988).…”
Section: Discussionsupporting
confidence: 77%
“…Although only one serotype of TGEV was described [22], it has been suggested that antigenic variation of TGEV may occur in nature [17,25,44,52]. Delmas et al [6] reported that four antigenic sites (A, B, C and D) of TGEV are located on the N-terminal half of the S glycoprotein. Most of the neutralization-mediating determinants were found in the domain A-B, which was highly conserved among TGEV strains [4].…”
Section: Discussionmentioning
confidence: 99%
“…The antigenicity of the S glycoprotein domains A and B is determined by carbohydrate-induced conformational dependent epitopes [5]. Site C was composed of largely conformationindependent epitopes and showed slight variation among TGEV strains [6]. Epitopes involved in the antigenic variation of TGEV strains have been found outside the major neutralization domain and induced non-neutralizing antibodies [25,41].…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that the FIPV epitope clusters defined as site A/A' and site E/F are homologous to site A and site E/F of TGEV, respectively. TGEV site A MAbs were previously shown to cross-react with FIPV strain 79-1146 (Delmas et al, 1990). The homology between the S proteins of FIPV and TGEV is further substantiated by the fact that TGEV MAbs 25C9.3 and 25E4.3 were also capable of mediating ADE of FIPV infection of primary feline macrophages (Table 1).…”
mentioning
confidence: 65%
“…Considerable work has been done to characterize and physically to map epitopes on the S protein of T G E V (Correa et al, 1988(Correa et al, , 1990Delmas et al, 1986Delmas et al, , 1990Garwes et al, 1987;Gebauer et al, 1991;Posthumus et al, 1990;Simkins et al, 1989Simkins et al, , 1992. Although there is some confusion regarding site designations (see Posthumus et al, 1990, for clarification), most investigators agree that there are four major and one or two minor antigenic sites on the S protein of TGEV.…”
mentioning
confidence: 99%